2023
DOI: 10.3389/fpls.2022.1094049
|View full text |Cite
|
Sign up to set email alerts
|

Distinct leaf functional traits of Tamarix chinensis at different habitats in the hinterland of the Taklimakan desert

Abstract: Leaf functional traits reflect plant adaptive strategies towards environmental heterogeneity. However, which factor play the key role of plasticity of leaf functional traits among various variable environmental factors remains unclear in desert hinterland oasis area. Here, we analyzed variations in leaf water content (LWC), δ13C values of leaves (δ13C), specific leaf area (SLA), leaf organic carbon concentration (LOC), leaf total nitrogen concentration (LTN), leaf total phosphorus concentration (LTP), and leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Many studies have proved that plants in the desert change leaf functional traits to reduce water loss ‎[ 59 , 60 ]‎. A study on leaf functional traits of Disanthus cercidifolius var.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have proved that plants in the desert change leaf functional traits to reduce water loss ‎[ 59 , 60 ]‎. A study on leaf functional traits of Disanthus cercidifolius var.…”
Section: Discussionmentioning
confidence: 99%
“…The mean SLA of adult T . chinensis at the pure stand, mixed forest in the hinterland of the Taklimakan desert was 39.06±6.87 cm 2 ·g -1 ‎[ 59 ]. The mean SLA of Tamarix sp.…”
Section: Discussionmentioning
confidence: 99%
“…Trees in harsh, resource-scarce environments tend to have lower SLA and higher LDMC to maximize their lifespan, employing a conservative resource utilization strategy—slower investment–return [ 7 , 8 ]. Consequently, environmental factors play a crucial role in shaping the spatial variability of resource utilization strategies across different types of trees [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have found that climatic factors, especially temperature and precipitation, significantly affect tree nutrient utilization strategies [ 6 , 9 ]. Higher temperatures and abundant rainfall largely alleviate environmental survival stress for trees, leading them to allocate more resources to compete for light.…”
Section: Introductionmentioning
confidence: 99%
“…The "trade-off strategy" of plants determines the position of individuals in the community, which in turn affects the stable coexistence of multiple species. This not only helps to analyze the trade-offs of species at different elevational gradients but also helps to understand the differentiation of plant functions (Tayir et al, 2023).…”
Section: Introductionmentioning
confidence: 99%